A specter is haunting science, the specter of piracy : A case study on the use of illegal routes of access to scientific literature by Argentinean researchers - Zukerfeld, Mariano (2022)
The aim of this study is to investigate the different types of access to scientific literature used by Argentinean researchers. This paper focuses particularly on the extent to which the illegal route is resorted to, the motivations for resorting to it, representations of legality and moral acceptability, and the relationship between productivity and different access routes. In order to tackle these topics, a survey was carried out among CONICET researchers. The main findings are as follows. The use of the illegal route is massive and widespread; it does not replace but rather coexists with the use of legal routes; there is a striking disconnection between the representations of legality and morality, and the motivations for using the illegal route are both practical and axiological.